Localização de indústrias de reciclagem na cadeia logística reversa do coco verde - Schwartz Filho, Arliss José (2006)
This work aims at developing a mathematical model and a methodological approach for the location of recycling industries of green coconut residuals. The coconut hard cover can cause environmental impacts when discharged along the beaches or in land farming. These residuals can be recycled and transformed into fibres, a qualified and profitable use, that can also generate jobs and revenues. It is of great importance the location study, theme approached in the present study using the following methodological steps: the characterization of the reverse chain logistics of the green coconut; selection of the places that are potential candidates to settle the recycling industries; estimation of the residual amount that is produced, travel distances and costs; development of a model of mixed linear and no linear programming; and choice of the tools for solution of the model. The modeling takes into account the amount of recycling industries, its capacities, the best locations and the corresponding residual distribution, which minimize the costs of installation, operation, stock and transport. Ten scenarios related to the problem were created for Espírito Santo State combining the numbers of industries, capacities and locations, and varying the involved costs, the amount of residues and the life time of the industries. The mathematical model showed to be a quite useful tool for analysis of location problems, due to its operational simplicity as well as the availability in the market of Solver and What´sBest!. As expected, the results agree with the reality of Espírito Santo State concerning the landfill location in the Cariacica district, actual place of destination of the green coconut residuals generated in the Grande Vitória region, being the same chosen in the ten used sceneries.